Vertical transmission of Tetracapsuloides bryosalmonae (Myxozoa), the causative agent of salmonid proliferative kidney disease - ABD-ELFATTAH, AHMED; FONTES, INÊS; KUMAR, GOKHLESH; SOLIMAN, HATEM; HARTIKAINEN, HANNA; OKAMURA, BETH; EL-MATBOULI, MANSOUR (Parasitology, 2014)
The freshwater bryozoan, Fredericella sultana, is the main primary host of the myxozoan endoparasite, Tetracapsuloides bryosalmonae which causes proliferative kidney disease (PKD) of salmonid fish. Because spores that develop in bryozoan colonies are infectious to fish, bryozoans represent the ultimate source of PKD. Bryozoans produce numerous seed-like dormant stages called statoblasts that enable persistence during unfavourable conditions and achieve long-distance dispersal. The possibility that T. bryosalmonae may undergo vertical transmission via infection of statoblasts has been the subject of much speculation since this is observed in close relatives. This study provides the first evidence that such vertical transmission of T. bryosalmonae is extensive by examining the proportions of infected statoblasts in populations of F. sultana on two different rivers systems and confirms its effectiveness by demonstrating transmission from material derived from infected statoblasts to fish hosts. Vertical transmission in statoblasts is likely to play an important role in the infection dynamics of both bryozoan and fish hosts and may substantially contribute to the widespread distribution of PKD.